1998
DOI: 10.1037/h0089865
|View full text |Cite
|
Sign up to set email alerts
|

Chronic illness in the context of marriage: A systems perspective of stress and coping in chronic obstructive pulmonary disease.

Abstract: CHRISTINE A. CANNON, PH.D. (FAMILY STUDIES), RNf JOHN C. CAVANAUGH, PH.D. (PSYCHOLOGY)*This document is copyrighted by the American Psychological Association or one of its allied publishers. This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 57 publications
3
48
0
3
Order By: Relevance
“…Common dyadic coping refers to trying to cope together, discussing the problem and searching for solutions (Bodenmann 2008). Apart from the patients' limited ability to engage in these activities as the disease progresses, it could also be possible that spouses start to hold back from expressing feelings of stress, wear an ''emotional straitjacket'', and try to protect their ill partners from strong emotions, and hence, breathing difficulties (Cannon and Cavanaugh 1998). This form of pro- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common dyadic coping refers to trying to cope together, discussing the problem and searching for solutions (Bodenmann 2008). Apart from the patients' limited ability to engage in these activities as the disease progresses, it could also be possible that spouses start to hold back from expressing feelings of stress, wear an ''emotional straitjacket'', and try to protect their ill partners from strong emotions, and hence, breathing difficulties (Cannon and Cavanaugh 1998). This form of pro- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with patients suffering from terminal lung cancer, health-related quality of life in COPD is even worse (Gore et al 2000;Habraken et al 2009). The patients' disease also impacts their partners' well-being and quality of life (Bergs 2002;Cannon and Cavanaugh 1998;Grant et al 2012;Hynes et al 2012;Kanervisto et al 2007a; Kanervisto et al 2007b;Keele-Card et al 1993;Rees et al 2001;Sexton and Munro 1985). Spouses' health-related quality of life is considerably lower compared to samples similar in age (Kühl et al 2008;Thöne et al 2011), and it tends to be even lower than patients' quality of life (Rees et al 2001).…”
Section: Introductionmentioning
confidence: 95%
“…2,3 It has been suggested that illness-related changes among patients with COPD lead to financial strain, shifts in marital roles and responsibilities, decreases in social and sexual activities, and increases in caregiving responsibilities for the spouse or significant other. 4 Studies of patients with chronic health problems (eg, cancer and coronary heart disease) have demonstrated that being married and having positive marital adjustment are associated with reduced morbidity and mortality. 5 In a comprehensive review of the research literature on health and marital quality, Kiecolt-Glaser and Newton 6 concluded that positive marital quality and marital interactions, not just marital status, affect health outcomes directly and indirectly, as reflected in reduced mortality and morbidity as well as enhanced immune functioning.…”
mentioning
confidence: 99%
“…Dieser physiologische Teufelskreis wird h ä ufi g durch psychische St ö rungen -besonders durch Angstst ö rungen und Depressionen erweitert [5 -7] . Gerade im psychosozialen Bereich lassen sich aufgrund der steigenden Dauerbelastung nicht nur bei Patienten, sondern auch bei ihren Angeh ö rigen Beeintr ä chtigungen erwarten und -wie in dem bisher einzigen Review zu diesem Thema beschriebenauch fi nden [8] : H ä ufi g steigt mit den pfl egerischen Bed ü rfnissen die fi nanzielle Belastung; gleichzeitig nehmen Freizeit und damit M ö glichkeiten, sozialen Aktivit ä ten nachzugehen, ab [8] . Die Angeh ö rigen m ü ssen emotionale Unterst ü tzung leisten, bekommen Erstickungsanf ä lle der Patienten mit und m ü ssen letztendlich u. U. sogar ü ber deren lebenserhaltende Ma ß -nahmen entscheiden [9] .…”
unclassified
“…In den gegenw ä rtig existierenden Querschnittstudien [10 -12] mit vorwiegend geringer Patientenanzahl [13] l ä sst sich der Zusammenhang zwischen den betrachteten Variablen auf seine Wirkungsrichtung hin nicht beurteilen. Zusammenfassend l ä sst sich aber feststellen, dass viele Angeh ö rige ihr Familienleben als durch die Erkrankung stark beeinfl usst wahrnehmen [8,11] , dass Ehepartner von COPD-Erkrankten erh ö hte Einsamkeitsund Depressionswerte aufweisen [12] und ü ber mangelnde Unterst ü tzung klagen [12,13] . Auch K ü hl et al berichten auf Grundlage der zur Baseline am vorliegenden Partnerkollektiv gewonnenen Daten von einer erh ö hten Pr ä valenz der Angst-und depressiven St ö rungen [14] .…”
unclassified